TINDAKAN MANUSIA MENURUT FAHAM FALSAFAH KALAM DALAM ISLAM - Syukri UR (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
The philosophy of kalam is an integral part of the basic teachings of a religion adopted by a Muslim. But it is rather strange, if it is said that in the History of Islamic Civilization, the first problem that arises is in the field of politics and not on the issue of theology. But this political problem soon increased rapidly to become a matter of theology. Islamic theology which is the main core of its discussion covers the basic issues of aqeedah and basic questions such as divinity, faith, kufr and nifak, as well as several other basic things as included in the scope of the pillars of faith.Keywords: Human, Ideology, Philosophy Ofalam, Islam